Confocal Arthroscopic Assessment of Osteoarthritis In Situ - Smolinski, D.; Jones, C.; Wu, Jian-Ping; Miller, K.; Kirk, T.; Zheng, M. (2008)
Purpose: This study aimed to assess the ability of the laser scanning confocal arthroscope (LSCA) to evaluate cartilage microstructure, particularly in differentiating stages of human osteoarthritis (OA) as classified by the International Cartilage Repair Society (ICRS) OA grade definitions. Methods: Ten tibial plateaus from total knee arthroplasty patients were obtained at the time of surgery. Cartilage areas were visually graded based on the ICRS classification, imaged by use of a 7-mm-diameter LSCA (488-nm excitation with 0.5% [wt/vol] fluorescein, 20-minute staining period), and then removed with underlying bone for histologic examination with H&E staining. The 2 imaging techniques were then compared for each ICRS grade to ascertain similarity between the methods and thus gauge the techniques' diagnostic resolution. Cartilage surface degeneration was readily imaged and OA severity accurately gauged by the LSCA and confirmed by histology. Results: LSCA and histologic images of specimens in the late stages of OA were seen to be mutually related even though they were imaged in planes that were orthogonal to each other. Useful and comparable diagnostic resolution was obtained in all imaged specimens from subjects with various stages of OA. Conclusions: This study showed the LSCA's ability to image detailed cartilage surface morphologic features that identify grade 1 through 4 of the ICRS OA grading system. The LSCA's imaging potential was best shown by its ability to resolve the fine collagen network present under the lamina splendens. The incorporation of high-magnification confocal technology within the confines of an arthroscopic probe has proved to provide the imaging requirements necessary to perform detailed cartilage condition assessment. Clinical Relevance: In comparison to video arthroscopy, LSCA provides increased magnification along with improved contrast and resolution. © 2008 Arthroscopy Association of North America.